Association between vaccination and days of hospitalization in adult patients with non-severe COVID-19 - Ding, Xiao; Ye, Jiru; Tang, Yao; Zhu, Feng (The Journal of Infection in Developing Countries, 2024)
Introduction: To explore the association between vaccination status and the days of hospitalization in non-severe adult COVID-19 patients. Methodology: We retrospectively analyzed the 368 non-severe adult COVID-19 patients which were divided into three groups according to their vaccination status. Univariate and multivariate linear regression analysis were performed to determine the correlation between vaccination and the days of hospitalization. A generalized additive model and hierarchical linear regression model were used for outcome analysis. Results: In the regression equation, the increase in the number of vaccine shots was significantly correlated with the decrease in the days of hospitalization (all p < 0.001). Particularly, the reduction of the days of hospitalization in patients with 3 injections of the vaccine was more significant than that of the 0-1 injection group (β: -2.810, -2.525, and -2.831; p < 0.001). Curve fitting showed that the relationship between the number of vaccination injections and the days of hospitalization was approximately linear, and the β value was -1.522 (95% CI: -2.091 − -0.954; p < 0.001). Among various laboratory indexes, only the monocyte ratio significantly affected the correlation between the number of vaccination injections and the days of hospitalization, indicating an interaction (p =0.027). The β values of the monocyte ratio in normal and elevated groups were -2.230 (95% CI: -3.048 − -1.412; p < 0.001) and -0.763 (95% CI: -1.520 − -0.005; p = 0.050), respectively. Conclusions: In non-severe adult COVID-19 patients, there was a negative linear correlation between the vaccination status and the days of hospitalization.